AN ANALYSIS OF WORD FORMATION USED IN POLITICAL ARTICLES OF THE JAKARTA POST NEWSPAPER - Handayani, Rindu (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2018)
This study aims to acknowledge what kind of word formation used in political articles of the Jakarta Post newspaper. The study is a descriptive qualitative research which used documentation method. The object of the study was to find out the word formation used and mostly used in political article which contains political words of the Jakarta Post newspaper. The articles chosen based on their political topics and the most frequency political discussion. The result of the study shows that, 95 political words were found in political articles of the Jakarta Post newspaper. Seventy five words were analysed and classified by word formation processes due to their own word classes, and other 20 words were not classified as word formation processes as the theories of the study. The kind of word formation in the political words were 48 derivation words, 11 words of compounds, and 14 words were the shortening.